Factors that influence utilization of internet payment system in Malaysia from the individual users' perspective - Mohamad Amin, Muhamad Sade; Said, Mohd Fuaad; Choo, Wei Chong; Raja Yusof, Raja Nerina (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
The aims of this study are to identify factors that affect internet-payment system adoption by the Malaysian public, and to understand the effect of these factors on their behavior toward using the system. A self-administered questionnaire was utilised and responses from 308 individual users were collected and analysed using structural Equation Modeling (SEM) techniques. Findings showed that perceived usefulness, ease of use and social influence have an effect on the behavioral intention of users, which in turn, has an influence on the actual use of the system by the users. Moreover, it was also found that perceived risk has a mediating effect on the relationship between trust and behavioral intention to usage. Findings from this study contribute to the literature of user acceptance of Information systems and can assist service providers, such as Malaysian commercial banks and government agencies, in improving their online payment systems that are offered to the general public.